Extensions for certain subordination relations - Kuroki, Kazuo (TWMS journal of applied and engineering mathematics, 2014)
For some complex number [gamma] which has a positive real part, a certain subordination relation concerned with the Bernardi integral operator [I.sub.[gamma]] was proven by D. J. Hallenbeck and St. Ruscheweyh (Proc. Amer. Math. Soc. 52(1975), 191-195). By considering the analyticity of the functions defined by the Bernardi integral operator [I.sub.[gamma]] for some non-zero complex number [gamma] with Re [gamma] [less than or equal to] 0, an extension for certain subordination relation are discussed. Keywords: Analytic function, Univalent function, Integral operator, Subordination. AMS Subject Classification: Primary 30C45.